Identificação molecular de tubarões do gênero Sphyrna sp. (Elasmobranchii, Chondrichthyes) da costa do Maranhão - Sodré, Camilla Fernanda Lima (2019)
The Sphyrna are globally under intense fishing exploitation and are classified, according to the IUCN, as species at risk of extinction. In the north coast of Brazil, this family has great expressiveness in fishing landings, in studies carried out they mention the occurrence of four species of Sphyrna for this region, being two coastal-oceanic (Sphyrna lewini and Sphyrna mokarran) and two small coastal-estuarine (Sphyrna tiburo and Sphyrna tudes). However, due to the difficulty of specific identification when landed, because they are processed as "cartridge", most of the records only report the genus Sphyrna. To assess the effectiveness of DNA barcode and ITS2 gene fragments in identifying hammerhead shark species, as well as determining which species are most frequently captured, we employ these molecular tools to identify muscle tissue samples acquired at major fishing ports. After DNA extraction and amplification, we sequenced the mitochondrial cytochrome oxidase subunit I (COI) gene and compared these sequences to those available in the Barcode of Life Database (BOLD) and NCBI GenBank. A total of 46 sequences were obtained indicating Sphyrna mokarran (67%), Sphyrna lewini (15%) and Sphyrna tudes (3%) and Sphyrna tiburo (15%), both listed as endangered species by IUCN and legally protected by IUCN. Ordinance 445/2014 (Endangered / Critically Endangered). Phylogenetic analysis using IOC revealed well supported clades for each of the four species described for the north coast of the MA. For Sphyrna lewini and for Sphyrna tiburo it was observed intra-specific genetic structuring. For the ITS2 gene, we used the Ambiercrombie protocol (2005), however, we suggest the optimization of the technique through the use of new primers. We can state that DNA barcoding is an efficient and accurate identification tool for Sphyrna species. Thus, molecular identification can contribute to control, control and monitoring of the fishing of the northern coast of Maranhão